2020
DOI: 10.33395/owner.v4i2.250
|View full text |Cite
|
Sign up to set email alerts
|

Kepemilikan Manajerial dan Praktik Penghindaran Pajak

Abstract: This study test the effect of managerial ownership on propensity of tax avoidance behaviour. Data used in this study were obtained from Indonesian stock exchange database and company's annual report. The author uses regression analysis with unbalanced panel data types from a sample of 144 manufacturing companies covering years period of 2015 to 2017. Propensity of tax avoidance as a dependent variable is measured by effective tax rate (ETR). The independent variable is managerial ownership which is determined … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 2 publications
1
3
0
1
Order By: Relevance
“…But on the other hand, there are also family company owners who use their power to gain benefits for their extended family. This has been proven in previous research (Zulma, 2016), (Subagiastra, Arizona, & Mahaputra, 2017), (Gaaya, Lakhal, & Lakhal, 2017), (Prastiwi & Ratnasari, 2019), (Niandari, Yustrianthe, & Grediani, 2020).…”
Section: Introductionsupporting
confidence: 79%
“…But on the other hand, there are also family company owners who use their power to gain benefits for their extended family. This has been proven in previous research (Zulma, 2016), (Subagiastra, Arizona, & Mahaputra, 2017), (Gaaya, Lakhal, & Lakhal, 2017), (Prastiwi & Ratnasari, 2019), (Niandari, Yustrianthe, & Grediani, 2020).…”
Section: Introductionsupporting
confidence: 79%
“…Pihak yang dimaksud adalah masyarakat, pemerintah, pelanggan, pemasok, dan kreditur. Sejalan dengan pendekatan ini, para pemangku kepentingan yang dianggap mempunyai kekuasaan untuk mempengaruhi bagaimana sumber daya ekonomi digunakan untuk memberi manfaat bagi pemangku kepentingan lainnya, khususnya masyarakat dan lingkungan hidup, mendapat perhatian khusus (Niandari, Nanik, 2022).…”
Section: Teori Stakeholderunclassified
“…(Jefri & Khoiriyah, 2019) concluded that ownership has a positive effect on tax avoidance. Research (Niandari et al, 2020;Ramdhani et al, 2020) explains that there is a positive effect between managerial ownership and tax avoidance. H4: Managerial Ownership has a positive impact on tax avoidance…”
Section: Influence Managerial Ownership On Tax Avoidancementioning
confidence: 99%